2009
DOI: 10.1007/s10545-009-1137-5
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset hyperargininaemia: A severe disorder?

Abstract: Early identification and management of this rare but potentially treatable affection is crucial as delayed management may result in poor neurological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…It presents as a progressive neurologic impairment with spasticity during childhood. ALF has been described in some acute-onset cases, with normalization under treatment (Schiff et al 2009), as well as hepatomegaly (Cederbaum et al 1979;Crombez and Cederbaum 2005) and severe neonatal cholestasis (Scaglia and Lee 2006). Hepatomegaly with fatty liver (Jordá et al 1986) and coagulopathy, cirrhosis complicated with portal hypertension, ESLD, and HCC complicating cirrhosis in a 22-year-old woman (Tsang et al 2012) have been described and can occur without encephalopathy (Braga et al 1997;Scaglia et al 2004;Edwards et al 2009;T s a n ge ta l2012).…”
Section: Arginase Deficiency (Argd; Omim 207800)mentioning
confidence: 99%
“…It presents as a progressive neurologic impairment with spasticity during childhood. ALF has been described in some acute-onset cases, with normalization under treatment (Schiff et al 2009), as well as hepatomegaly (Cederbaum et al 1979;Crombez and Cederbaum 2005) and severe neonatal cholestasis (Scaglia and Lee 2006). Hepatomegaly with fatty liver (Jordá et al 1986) and coagulopathy, cirrhosis complicated with portal hypertension, ESLD, and HCC complicating cirrhosis in a 22-year-old woman (Tsang et al 2012) have been described and can occur without encephalopathy (Braga et al 1997;Scaglia et al 2004;Edwards et al 2009;T s a n ge ta l2012).…”
Section: Arginase Deficiency (Argd; Omim 207800)mentioning
confidence: 99%
“…Symptoms in the neonatal period include hepatomegaly, neonatal cholestasis, and liver failure but also drowsiness, seizures and cerebral edema with mild or moderate elevations of ammonia of up to 250 µmol/l (Jorda et al 1986;Picker et al 2003;Braga et al 1997;Schiff et al 2009). Interestingly, there are no reports of cases of severe hyperammonemia in the first days of life as typically seen in other urea cycle disorders.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies have shown variable cerebral and less often cerebellar atrophy (Gungor et al 2008;Carvalho et al 2012b;Schiff et al 2009), ischemic changes and edema, signal changes in the posterior putamina and insular cortex (Gungor et al 2008), and abnormal myelination (Brockstedt et al 1990). Similar findings are recognized in most other UCDs in which hyperammonemia is a pathophysiologic factor (Blaser and Feigenbaum 2004).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Neonatal presentation of ARG1 deficiency with significant hyperammonemia is rare and only six case reports exist in the literature [7, 8, 9, 10, 11, 12]. In this report, we present an additional infant with ARG1 deficiency with hyperammonemia and compare the clinical and biochemical features of the proband and review the existing literature.…”
Section: Introductionmentioning
confidence: 97%